2021
DOI: 10.3389/fpls.2021.740456
|View full text |Cite
|
Sign up to set email alerts
|

“Breeding on Mountains” Resulted in the Reorganization of Endophytic Fungi in Asexually Propagated Plants (Ligusticum chuanxiong Hort.)

Abstract: “Breeding on mountains, cultivation in dam areas” is a unique propagation method for the vegetatively propagated plant Ligusticum chuanxiong, including two transplants between the mountain and the dam area. It is well known that the environment can influence the endophytic community structure of plants. However, the change of host endophytic flora caused by transplanting in different places and its influence on asexual reproduction are still poorly understood. We carried out three cycles of cultivation experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 80 publications
0
5
1
Order By: Relevance
“…These results showed that, after transplanting, LZ endophytic bacteria recombined. The degree of recombination of endophytic bacteria community caused by local transplanting was greater than that caused by mountain transplanting, which was just opposite to the recombination of fungal community of L. chuanxiong in the previous study ( Kang et al, 2021 ). This might be related to the species diversity of the bacterial community in the soil: the species diversity in the mountain soil was lower than that in the dam soil.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…These results showed that, after transplanting, LZ endophytic bacteria recombined. The degree of recombination of endophytic bacteria community caused by local transplanting was greater than that caused by mountain transplanting, which was just opposite to the recombination of fungal community of L. chuanxiong in the previous study ( Kang et al, 2021 ). This might be related to the species diversity of the bacterial community in the soil: the species diversity in the mountain soil was lower than that in the dam soil.…”
Section: Discussioncontrasting
confidence: 72%
“…In our previous research, we found that the process of mountain breeding led to the recombination of endophytic fungi in LZ, with more disease resistant fungi and growth promoting fungi in the LZ, while the pathogenic fungi were reduced in it. These recombinated fungi were proveded could promote the growth and development of host and resist pathogenic bacteria ( Kang et al, 2021 ). This study focused on the endophytic bacterial community structure in the process of propagation and transplantation of L. chuanxiong , hoping to clarify the microecological reorganization mechanism caused by the transplantation process and its contribution to the rejuvenation of asexual plant germplasm.…”
Section: Introductionmentioning
confidence: 99%
“…At genus resolution, plant samples showed a high abundance of genera that have been already described as endophytes: Exophiala (Yu et al, 2021), Monosporascus (Guo and Zou, 2020), Paraphoma (Kang et al, 2021), Plectospherella (Feng et al, 2021;Wei et al, 2021), Podospora (Penner and Sapir, 2021). Some of these genera were even identified in Brassicaceae plant endospheres, including Exophiala (Maciá-Vicente et al, 2016), Plectosphaerella (Plaszkó et al, 2020;Ważny et al, 2021), Setophoma (Szűcs et al, 2018;Poveda et al, 2020), or as a common pathogen: Thanatephorus (teleomorph of Rhizoctonia) (Dean et al, 2012).…”
Section: Fungal Community Composition and Diversitymentioning
confidence: 99%
“…However, environmental factors have been reported to shape the endophytic fungal community structure, resulting in differences in plant characteristics (Coleman-Derr et al, 2016;. Transplantation of plants from dam areas to mountains can lead to the recombination of endophytic fungi and alter the diversity and richness of endophytic fungi in Ligusticum chuanxiong (Kang et al, 2021). Interestingly, a study indicated that five secondary metabolites, namely aloe-emodin, rhein, emodin, chrysophanol, and physcion, are positively correlated with the diversity and abundance of endophytic fungi of Rheum palmatum from eight different production areas (Chen D. et al, 2021).…”
Section: Introductionmentioning
confidence: 99%